Cottage by the Sea - Novel - Macomber, Debbie; Vacker, Karissa (Random House Audio, 2018)
Annie Marlow has been through the worst. Rocked by tragedy, she heads to the one place that makes her happy: Oceanside in the Pacific Northwest, the destintation of many family vacations when Annie was a teenager. Once there, Annie begins to restore her broken spirit, thanks in part to the folks she meets: a local painter, Keaton, whose large frame is equal to his big heart--and who helps Annie fix up her rental cottage by the sea; Mellie, the reclusive, prickly landlord Annie is determined to befriend; and Britt, a teenager with a terrible secret. But it is Keaton to whom Annie feels most drawn. His quiet, peaceful nature offers her both comfort and reprieve from her grief, and the two begin to grow closer. Then events threaten to undo the idyll Annie has come to enjoy. And when the opportunity of a lifetime lands in her lap, she is torn between the excitement of a new journey toward success and the safe and secure arms of the haven--and the man-shes come to call home.
Keywords: Man-woman relationships -- Fiction; Friendship -- Fiction; Audiobooks; Romance fiction